MENGHADAPI INFLASI: STRATEGI PENGENDALIAN DAN DAMPAK TERHADAP EKONOMI DAN KESEJAHTERAAN RAKYAT - Heti Nurhasanah; Ferdy Agung Nugroho (Pusat Riset dan Inovasi Nasional, 2024)
: In the last decade, inflation has become one of the main challenges faced by many countries, including Indonesia, which has an impact on economic stability and people’s welfare. Research Phenomenon: Inflation, defined as a general and sustained increase in prices, often erodes people’s purchasing power and causes economic instability, which in turn affects people’s overall welfare. This research problem focuses on how to identify effective inflation control strategies and understand their impact on the economy and people’s welfare. The aim of this research is to explore and analyze various inflation control strategies that have been implemented in Indonesia and to assess the implementation and effectiveness of these strategies in stabilizing prices and minimizing negative impacts on the economy and people’s welfare. This research uses a qualitative method with a case study approach. This approach was chosen to gain an in-depth understanding of the complexity of the inflation phenomenon, the control strategies that have been implemented, as well as society’s perceptions and responses to these strategies. The research results show that although there are various efforts to control inflation, such as tight monetary policy and controlling prices of basic commodities, there are still challenges in implementation, including coordination between institutions and market response. Another important finding is that the success of controlling inflation is not only measured by price stability, but also by society’s ability to maintain their welfare. This study proposes that an effective inflation control strategy must be accompanied by supportive social policies, such as social assistance for low-income people, to maintain people’s welfare.